1994
DOI: 10.1016/0378-1097(94)90044-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanisms of xylose uptake in the thermophilic bacterium Thermoanaerobacter thermohydrosulfuricus

Abstract: Thermoanaerobacter thermohydrosulfuricus Rt8.BI catabolized xylose by the pentose phosphate pathway, and xylose isomerase and xylulokinase were inducible. The uptake of xylose was by two low-affinity, inducible systems. Both systems were resistant to the protonophore, tetrachlorosalicylanilide, the FIF0-ATPase inhibitor, N,N-dicyclohexylcarboiimide, and the sodium/ proton antiporter, monensin. The high capacity system (100 nmol rain I (rag protein) -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…No diauxic shifts were observed and carbohydrates were simultaneously utilised in all of the carbohydrate combinations tested (Supplementary Figure 4), indicating a lack of carbon catabolite repression and non-diauxic growth. Non-diauxic growth has been observed previously in Sulfolobus acidocaldarius and Thermoanaerobacter thermohydrosulfuricus, and was attributed to the lack of a carbohydrate phosphotransferase system (PTS; Cook et al, 1993Cook et al, , 1994Joshua et al, 2011). The T49 T genome also lacks any transporter genes associated with PTS.…”
Section: Regulation Of Carbohydrate Metabolismmentioning
confidence: 90%
“…No diauxic shifts were observed and carbohydrates were simultaneously utilised in all of the carbohydrate combinations tested (Supplementary Figure 4), indicating a lack of carbon catabolite repression and non-diauxic growth. Non-diauxic growth has been observed previously in Sulfolobus acidocaldarius and Thermoanaerobacter thermohydrosulfuricus, and was attributed to the lack of a carbohydrate phosphotransferase system (PTS; Cook et al, 1993Cook et al, , 1994Joshua et al, 2011). The T49 T genome also lacks any transporter genes associated with PTS.…”
Section: Regulation Of Carbohydrate Metabolismmentioning
confidence: 90%
“…Indirect evidence based on the effects of metabolic inhibitors and uncouplers on glucose transport in Clostridium thermocellum and C. thermohydrosulfuricum (now Thermoanaerobacter thermohydrosulfuricus) has suggested that transport is dependent on ATP rather than a proton or sodium gradient (15,29). Recently, it has been proposed that glucose and xylose are taken up by Thermoanaerobacter thermohydrosulfuricus through a facilitated diffusion mechanism (8,9). On the other hand, in C. thermosulfurogenes EM1 (now Thermoanaerobacterium thermosulfurigenes), two genes, amyC and amyD, which are homologous to two membrane components of the maltose and glycerol-3-phosphate transport systems of E. coli, were found (3).…”
mentioning
confidence: 99%
“…This study has demonstrated that the Gram‐positive, broad host range plasmid pUB110 can be introduced by electroporation into eight strains of Bu. fibrisolvens , representing all three groups currently recognized by 16S rRNA‐based phylogeny (Cook et al . 1994; Forster et al .…”
Section: Discussionmentioning
confidence: 99%